PREDIKAT KOMPLEKS BAHASA ACEH: KAJIAN TEORI X-BAR - DARA MUBSHIRAH; Mulyadi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to analyze complex predicates in Acehnese in the sentence structure used by speakers in everyday life. This study uses a qualitative approach with descriptive analysis method. The object of research is the predicate of the Acehnese language complex. The data sources for this research are three native Acehnese speakers. Data collection by observation and interview methods. Analysis was carried out during collection, reduction, presentation, and drawing conclusions/verification. Data analysis uses distributional and substitutional methods. The results of the study show that the characteristics of complex predicates in the Acehnese language are as follows. (1) Complex predicates are formed from two or three verbs, (2) complex predicates are located side by side, (3) complex predicates form one event (single predicate), and (4) have the same aspect or negation. There are four patterns for forming complex predicates in Acehnese, namely: (1) intransitive V1 + intransitive V2, (2) transitive V1 + intransitive V2, (3) intransitive V1 + transitive V2, (4) transitive V1 + transitive V2, and (5) intransitive V1 + intransitive V2 + transitive V3